(untitled) (Praxis Educativa, 2026)
Social work can play a fundamental role in promoting active citizenship, so its training must incorporate the development of civic competencies. This article presents the conceptions of citizenship among students beginning their social work training at a state university in southern Chile. The approach is qualitative; the data generation technique is a self-administered questionnaire administered to students just beginning their first academic semester, within the framework of a general education course; the analytical matrix is ​​structural analysis. The results show an understanding of citizenship as local belonging based on residence, with abstract rights and duties. Furthermore, they highlight the centrality of political participation rights as the primary role of the State, although limited to an institutional vision that is not perceived as transformative. Finally, a weak identity affiliation is identified, associated with smaller political entities.